HMGA1/HMGA2 protein expression and prognostic implications in gastric cancer. (December 2015) - Jun, Kyong-Hwa; Jung, Ji-Han; Choi, Hyun-Joo; Shin, Eun-Young; Chin, Hyung-Min
Abstract: Background: The high mobility group A1 (HMGA1) and high mobility group A2 (HMGA2) proteins are architectural transcription factors that have been implicated in the pathogenesis and progression of multiple malignant tumors, including gastric cancer. The aim of this study was to explore the roles of HMGA1 and HMGA2 in gastric carcinogenesis. Methods: The expression of HMGA1 and HMGA2 was examined in 110 gastric adenocarcinomas, 29 gastric adenomas, and 30 normal controls. The results were correlated with the clinicopathological parameters of the tumors and patient outcome. Results: The levels of HMGA1 and HMGA2 proteins were significantly increased in gastric cancer samples compared with adenoma and normal gastric tissues. High HMGA1 nuclear immunoreactivity was not correlated with clinicopathological features; however, high levels of HMGA2 protein were significantly associated with T stage, N stage, lymphatic invasion, perineural invasion, and TNM stage. Moreover, HMGA2 expression was significantly associated with shorter recurrence free survival. Multivariate analysis showed that HMGA2 expression was an independent prognostic factor for tumor recurrence. Conclusions: Our results suggest that HMGA1 and HMGA2 are implicated in gastric carcinogenesis and may play a role in tumor progression towards a more malignant phenotype. The HMGA2 protein may be a useful prognostic marker for predicting tumor recurrence. Highlights: HMGA2 is associated with clinicopathologic feature in gastric cancer. HMGA2 expression is associated with shorter recurrence free survival. HMGA2 expression is an independent prognostic factor for tumor recurrence.